A STUDY OF ACTIVISM, LEVEL OF ASPIRATION AND ACADEMIC ACHIEVEMENT OF SOCIALLY AND ECONOMICALLY DEPRIVED - Neelam, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The main basic function of education society is to develop skills, knowledge and awareness of our national and international heritage and the achievement of human people, possessing a essential technical outlook and commitment to the ideals of patriotism, democracy, secularism, socialism, peace and the principles enunciated in the Preamble to our Constitution. The education sector has to produce leaders of society in all areas of activities with a commitment to the above ideals. according to Education in traditional values with our national needs and priorities make sure that our best talents make befitting contributions on societal needs. Education is the main instrument of social change and national reconstruction. Through education we prepare the young generation of today to reconstruct the nation, the citizen of tomorrow. The schools are engaged in this important task of preparing the future nation builders. On the quality and number of persons coming out of our schools and colleges depends our success in the great enterprise of national reconstruction, whose belief objective is to raise standard of living of our people. But society of education are normally weak among many Dalits, tribals and other deprived social groups and a positive outlook is harder to build. The way the schools function, stand for and support somewhat than question, the accessible social and gender division make it more difficult to break the ferocious circle that keeps children away from school in poor families. Poverty and a defenseless life-situation add to common social practices in keeping these children in no-win situations. Poverty is widespread in India, with the nation likely to have one third of the world's poor.......